Depression of central respiratory drive by nitrazepam. Issue 1 (February 1978) - Rudolf, M; Geddes, D M; Turner, J A; Saunders, K B
Abstract : In a group of patients with chronic bronchitis, repeated night sedation with 10 mg nitrazepam produced a fall in central respiratory drive and a steady rise in arterial carbon dioxide tension. The changes produced over a five-day period were not clinically important, except in two patients who were already hypercapnic before receiving nitrazepam. The use of this drug in patients with carbon dioxide retention should be avoided.